My Back Exercise app: an automated exercise intervention supported by educational notifications, a sleep programme and diet advice to improve function in people with chronic non-specific low back pain – protocol for a superiority, adaptive multi-arm multi-stage randomised controlled trial - Manuela L Ferreira; Kim L Bennell; Christopher J Gordon; Josielli Comachio; Paulo Ferreira; Rachel K Nelligan; Serigne N Lo; Paula Beckenkamp; Anelise Moreti Cabral Silveira; Carlos Mesa-Castrillon; Katharine Roberts; Emma K Ho; et al. (BMJ Open)
Introduction As chronic low back pain (LBP) remains one of the most pressing global health challenges, digital health emerges as an opportunity to deliver evidence-based care at scale. In this context, the My Back Exercise app has been developed to support people with LBP in self-managing their condition. This study aims to determine the effectiveness of the My Back Exercise app to improve physical function in people with chronic non-specific LBP.Methods and analysis A single-blind, superiority, adaptive randomised controlled trial encompassing a multi-arm multi-stage design will be conducted and reported according to the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT), Template for the Intervention Description and Replication for telehealth (TIDieR-telehealth), and the Consolidated Standards of Reporting Trials (CONSORT) Extension for Adaptive Designs. Informed consent will be obtained from all participants. Eligible participants will be randomly assigned in a 1:1:1:1:1 ratio to either the control group, receiving education alone, or one of four intervention groups ((1) education, notifications and exercise modules; (2) education, notifications, exercise and sleep modules; (3) education, notifications, exercise and diet modules; and (4) education, notifications, exercise, sleep and diet modules) through the app. The study consists of two stages with the possibility of dropping arms for futility using pre-specified decision rules at the end of the first stage. A total of 370 participants aged 18 years or older, with chronic non-specific LBP, will be recruited Australia-wide from the general community. The primary outcome will be self-reported physical function measured by the Patient-Specific Functional Scale at 6 weeks post-randomisation. Data will be analysed using the Student’s t-test or the non-parametric Mann-Whitney U test.Ethics and dissemination This trial was approved by the Human Research Ethics Committee (HREC) of The University of Sydney (HREC Approval No. 2023/HE000772). The findings of this study will be disseminated via scientific publications, reports and conference presentations, and strategically disseminated to the wider community and relevant policymakers.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12624000319572).